Sociodemographic differences in health awareness and oral health in pregnant women = Soziodemografische Unterschiede im Gesundheitsbewusstseinund der Mundgesundheit bei Schwangeren - Kühle, Anna-Maria; Wacker, Jürgen (Geburtshilfe und Frauenheilkunde, 2020)
The aim of this study was to determine the present oral health status of pregnant women depending on selected sociodemographic differences and deduce any resulting consequences for health prevention. Methods The participantsʼ data of relevance to the study such as age, school leaving qualification, migration background, smoking habits or last dentist visit were recorded using a questionnaire. The subsequent dental check-up concentrated on open carious lesions, any initiated root canal treatments and missing teeth. Finally, the Periodontal Screening Index was recorded to diagnose the presence of any gingivitis or periodontitis. The subsequent biometric evaluation comprised descriptive data analysis, χ2 test and logistical regression. Results The higher the school leaving qualification, the lower the probability that a pregnant woman smoked prior to pregnancy (OR 0.291; 95% CI 0.114 - 0.743) and that tartar was diagnosed (OR 0.424; 95% CI 0.185 - 0.973). Regular dentist visits (OR 4.026; 95% CI 1.613 - 10.049) increase with the attained school leaving qualification. There is a greater chance that women born in Germany taking part in the study were aware of dental risks in pregnancy (OR 2.652; 95% CI 1.285 - 5.472) and attended the dentist during pregnancy (OR 2.507; 95% CI 1.281 - 4.907). Conclusion The rate of awareness of the risks and consequences of pregnancy for oral health must be increased. The main aim for primary prophylaxis should be a reduction in the periodontal bacteria and caries of the mother and father.